Determination of Lutein from Green Tea and Green Tea By‐Products Using Accelerated Solvent Extraction and UPLC. Issue 5 (23rd April 2014) - Heo, Ji‐Young; Kim, Suna; Kang, Jae‐Hyun; Moon, BoKyung
Abstract We aimed to identify the optimum conditions for the extraction of lutein from green tea using accelerated solvent extraction, and achieve improved analytical resolution and sensitivity between lutein and zeaxanthin using an ultra performance liquid chromatography (UPLC) system. The optimized method employed 80% ethanol as the extraction solvent, 160 °C as the temperature, 2 static cycles, and 5 min of static time. In the validation of the UPLC method, recovery was found to be in the range approximately 93.73 to 108.79%, with a correlation coefficient of 0.9974 and a relative standard deviation of <9.29% in inter‐ and intraday precision analyses. Finally, the lutein contents of green tea and green tea by‐products were measured as 32.67 ± 0.70 and 18.18 ± 0.68 mg/100g dw, respectively. Furthermore, we verified that green tea by‐products, which are discarded after producing green tea beverages, might be used as a great resource for massive lutein production. Practical Application We have demonstrated that the common problem of inadequate resolution between lutein and zeaxanthin during carotenoid analyses can be overcome by optimizing the combined techniques of accelerated solvent extraction and ultra performance liquid chromatography (UPLC). UPLC was highly effective for saving time, solvent, and labor, as well as providing better resolution. The results in this study demonstrated that green tea by‐products could be used as new sources for industrial lutein production owing to their massive production during the extraction of green tea beverages.